Korepin festschrift : from statistical mechanics to quantum information science : [a collection of articles written in honor of the 60th birthday of Vladimir Korepin] - Korepin, V. E. (Vladimir E.); Kwek, Leong Chuan; Severini, Simone (Physicist); Su, Haibin (International journal of modern physics. Condensed matter physics, statistical physics, applied physics, 2013)
This volume mainly summarizes the invited talks presented at the 5th Asia-Pacific Workshop on Quantum Information Science (APWQIS) in conjunction with a Festschrift in honor of Professor Vladimir Korepin's 60th birthday. In this Festschrift, we have assembled a medley of interesting articles from some of his friends, well-wishers and collaborators. Comprising both reviews of the state-of-the-art and the latest results, this book covers various aspects of quantum information science, including topics like quantum discord, quantum computing, quantum entanglement, etc.